2017
DOI: 10.1007/s00415-017-8676-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in disability in people with multiple sclerosis: a 10-year prospective study

Abstract: BackgroundLittle is known about the long-term course of disability in relation with disease severity in people with multiple sclerosis (PwMS).ObjectiveTo explore changes in a broad spectrum of disability over 10 years in relation with disease severity in PwMS.MethodsWe conducted a longitudinal study of 155 PwMS who attended the MS Centre at Karolinska University Hospital, Stockholm. Disease severity was determined by the use of the Expanded Disability Status Scale (EDSS) and classified as mild MS (EDSS score 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 39 publications
5
49
0
Order By: Relevance
“…In contrast, inconsistent findings have been reported with regard to participation in more complex social/lifestyle activities (e.g. work and social occasions); most studies have shown restricted participation in people with MS across 10 years [3,14,15] whereas others have demonstrated sustained [4] or improved participation [16]. The aforementioned longitudinal studies have reported changes in the sum score of items compromising instruments assessing ADL or participation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, inconsistent findings have been reported with regard to participation in more complex social/lifestyle activities (e.g. work and social occasions); most studies have shown restricted participation in people with MS across 10 years [3,14,15] whereas others have demonstrated sustained [4] or improved participation [16]. The aforementioned longitudinal studies have reported changes in the sum score of items compromising instruments assessing ADL or participation.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple sclerosis (MS) is a neuroinflammatory demyelinating disease causing progressive disability and resulting in a substantial burden for the individual and society [1,2]. As MS progresses, people with MS experience reduced ability to perform activities of daily living (ADL) and to participate in various life situations [2][3][4][5][6]; which in turn have a negative impact on their quality of life [2,7,8]. MS often results in different types of disability (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple Sclerosis (MS), is a neurodegenerative disorder that affects all aspects of life [1][2][3]. Fluctuating symptoms and a variable decline in functioning, can differentially impact upon perceived quality of life [4] .…”
Section: Introductionmentioning
confidence: 99%
“…This can be assessed using the Frenchay Activities Index (FAI), which provides an effective evaluation method that captures an individual's status of activities and participation. The FAI was originally developed to assess the status of instrumental activities of daily living (IADL) for stroke patients [12], and many studies have been conducted with patients with various illnesses and injuries, including lower limb amputation [13], multiple sclerosis [14], and spinal cord injury [15], and it has also been applied to the general elderly population [16]. The validity and reliability of various country-specific translations of the scales have been confirmed, including, for the Japanese, Chinese, and Korean versions [17] [18] [19].…”
Section: Introductionmentioning
confidence: 99%